Biology, ecology, and biotechnological applications of anaerobic bacteria adapted to environmental stresses in temperature, pH, salinity, or substrates. - Lowe, S E (1993)
Anaerobic bacteria include diverse species that can grow at environmental extremes of temperature, pH, salinity, substrate toxicity, or available free energy. The first evolved archaebacterial and eubacterial species appear to have been anaerobes adapted to high temperatures. Thermoanaerobes and their stable enzymes have served as model systems for basic and applied studies of microbial cellulose and starch degradation, methanogenesis, ethanologenesis, acetogenesis, autotrophic CO2 fixation, saccharidases, hydrogenases, and alcohol dehydrogenases. Anaerobes, unlike aerobes, appear to have evolved more energy-conserving mechanisms for physiological adaptation to environmental stresses such as novel enzyme activities and stabilities and novel membrane lipid compositions and functions. Anaerobic syntrophs do not have similar aerobic bacterial counterparts. The metabolic end products of syntrophs are potent thermodynamic inhibitors of energy conservation mechanisms, and they require coordinated consumption by a second partner organism for species growth. Anaerobes adapted to environmental stresses and their enzymes have biotechnological applications in organic waste treatment systems and chemical and fuel production systems based on biomass-derived substrates or syngas. These kinds of anaerobes have only recently been examined by biologists, and considerably more study is required before they are fully appreciated by science and technology.